Software Engineering A Methodical Approach - Foster, Elvis; SpringerLink (Online service) (Berkeley, CA : Apress : Imprint: Apress, 2014)
This text provides a comprehensive, but concise introduction to software engineering. It adopts a methodical approach to solving software engineering problems proven over several years of teaching, with outstanding results. The book covers concepts, principles, design, construction, implementation, and management issues of software systems. Each chapter is organized systematically into brief, reader-friendly sections, with itemization of the important points to be remembered. Diagrams and illustrations also sum up the salient points to enhance learning. Additionally, the book includes a number of the author’s original methodologies that add clarity and creativity to the software engineering experience, while making a novel contribution to the discipline. Upholding his aim for brevity, comprehensive coverage, and relevance, Foster’s practical and methodical discussion style gets straight to the salient issues, and avoids unnecessary topics and minimizes theoretical coverage.
Keywords: Software engineering; Software Engineering/Programming and Operating Systems